El Quijote de Coseriu - Wiesse Rebagliati, Jorge (2017)
In his extensive linguistic work, Eugenio Coseriu (Mihaileni, 1921 - Tübingen, 2002), uses literature several times to exemplify theoretical linguistic concepts and even to model them. As is the case with several 20th century scholars (José Ortega y Gasset or Mijaíl Bajtín), Don Quixote is, for Coseriu, a touchstone to formulate reflections that do not apply exclusively to it, as other relevant works of 20th century’s Cervantism, such as Stephen Gilman’s or and Edward C. Riley’s, do. This article seeks to trace the references of Don Quixote and Cervantes in Coseriu’s work and, above all, to present and discuss the correction made by Coseriu to Leo Spitzer’s “Perspectivismo lingüístico en el Quijote”.